A Service User Perspective Informing the Role of Occupational Therapy in School Transition Practice for High School Learners with TBI: An African Perspective - Lee-Ann Jacobs-Nzuzi Khuabi; Estelle Swart; Mogammad Shaheed Soeker (Occupational Therapy International)
Background. In the South African context, there are no specific guidelines regarding how to prepare and support adolescents for the transition from a health care to a high school setting post TBI. This raises questions about the relevance and responsiveness of the current transition practices in occupational therapy in terms of adequately preparing and supporting these adolescents to participate in school and hence exercise their right to a quality education. Method. This study explored adolescents and other key role players’ perspectives on and experiences of the high school transition (i.e., school reentry and continued school participation) post TBI. It was anticipated that this would provide an increased understanding of the enablers and barriers to high school reentry and participation post TBI. This served as a basis to explore the main aim of this study which was to help occupational therapists identify where efforts in terms of service delivery are needed. This study was situated in the interpretivist qualitative paradigm and used a multicase study design, which included semistructured interviews with eight adolescent learners with TBI, their primary caregivers, teachers, and principals as well as observations and documentation review. Results. This paper will focus on a central theme in the research, namely, the nature and extent of support needed to facilitate the high school transition of adolescents with TBI within a developing context. Similar to the findings of studies conducted in developed contexts, participants highlighted that they felt that adolescents need support at various stages of the school transition. Participants further alluded to support that should be collaborative, coordinated, flexible, and monitored to ensure it is relevant and responsive to these adolescents’ changing needs. Conclusion. The study findings conclude that occupational therapists have a crucial role in fostering an enabling environment (directly and indirectly) through fulfilling various roles including that of a facilitator, intermediary, coach, collaborator, supporter, and advocator.